Reshaping life after stroke: a grounded theory - Dagmar J.J. van Nimwegen; Sigrid C.J.M. Vervoort; Johanna M.A. Visser-Meily; Lisette Schoonhoven; Janneke M. de Man-van Ginkel (International Journal of Nursing Studies Advances)
Background: Stroke patients often experience different consequences, negatively impacting their psychosocial well-being. Since every patient has their individual process and their individual needs, providing personalised stroke care is difficult. Determining what is needed in stroke care is crucial to optimize well-being after stroke. Objective: To gain understanding of how patients experience the process they go through, which psychosocial needs they experience, and whether the current stroke care matches this process. Methods: A qualitative study according to the methodology of Grounded Theory, by conducting semi-structured interviews with ten stroke patients who were receiving stroke care in a stroke service. Results: Patients after stroke go through a basic social process of reshaping life which was characterized by two perspectives – feeling lost and rediscovering yourself. These perspectives could be refined on several themes: focusing on capabilities; setting goals; experiencing emotions; feeling heard or understood; and finding meaning in life. The following themes influence this process: help and understanding from patients’ network; patients’ needs being met in stroke care; and support and motivation from other patients. Conclusions: Healthcare professionals could use the found process of reshaping life to determine for each patient where they find themselves within this process. They can use this to determine which needs patients experience, and how they can match these needs to support patients in reshaping life to improve patients’ psychosocial well-being after stroke. Funding and registration: This study was supported by the Taskforce for Applied Research SIA (RAAK.PUB04.010) and was registered at the Dutch Trial Register (NL7440).